Agronomic traits and essential oil profiles of Humulus lupulus L. cultivated in southern Italy. Issue 1 (2nd January 2023) - Gresta, Fabio; Calvi, Antonio; Santonoceto, Carmelo; Strano, Tonia; Ruberto, Giuseppe
ABSTRACT: Humulus lupulus L. is a dioecious herbaceous perennial plant with a climbing habit, whose female inflorescences, commonly known as cones, produce and accumulate bitter substances and essential oils. The present study aimed to assess the adaptability of some American hop varieties (Cascade, Chinook, and Comet) in the Mediterranean environment of the Calabria region (Italy) through the evaluation of the morpho-biological and productive characteristics and the characterization of the aromatic traits of the inflorescences. Comet proved to be the most productive variety, while Chinook the earliest. Essential oils obtained by hydrdistillation were analysed by GC-FID and GC-MS. Myrcene, β-caryphyllene and α-humulene were the main components. The combination of morphological traits and the aromatic profiles could be adopted as tools to discriminate varieties. Comet was the most productive variety, while Chinook emerged as the earliest one. Concernng the essential oils Cascade and Comet showed similar profiles, Chinnok was different especially for the sesquiterpenes content.